The addition of an amylopectin/chromium complex to branched-chain amino acids enhances muscle protein synthesis in rat skeletal muscle - Komorowski, James R.; Ojalvo, Sara Perez; Sylla, Sarah; Tastan, Hakki; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Kazım (Taylor & Francis Inc, 2020)
BackgroundA previous clinical study reported that the addition of an amylopectin/chromium complex (ACr; Velositol (R)) to 6g of whey protein (WP) significantly enhanced muscle protein synthesis (MPS). Branched-chain amino acids (BCAAs) are also well-known to enhance MPS. The aim of this study was to determine if the addition of ACr to BCAAs can enhance MPS and activate expression of the mammalian target of the rapamycin (mTOR) pathway compared to BCAAs and exercise alone in exercise-trained rats.MethodsTwenty-four male Wistar rats were randomly divided into three groups (n=8 per group): (I) Exercise control, (II) Exercise plus BCAAs (0.465g/kg BW, a 6g human equivalent dose (HED)), and (III) Exercise plus BCAAs (0.465g/kg BW) and ACr (0.155g/kg BW, a 2g HED). All animals were trained with treadmill exercise for 10days. On the day of the single-dose experiment, rats were exercised at 26m/min for 2h and then fed, via oral gavage, study product. One hour after the consumption of study product, rats were injected with a bolus dose (250mg/kg BW, 25g/L) of phenylalanine labeled with deuterium to measure the fractional rate of protein synthesis (FSR). Ten minutes later, muscle tissue samples were taken to determine MPS measured by FSR and the phosphorylation of proteins involved in the mTOR pathway including mTOR, S6K1, and 4E-BP1.ResultsACr combined with BCAAs increased MPS by 71% compared to the exercise control group, while BCAAs alone increased MPS by 57% over control (p<0.05). ACr plus BCAAs significantly enhanced phosphorylation of mTOR, S6K1 and 4E-BP1 compared to exercise control rats (p<0.05). The addition of ACr to BCAAs enhanced insulin levels, mTOR and S6K1 phosphorylation compared to BCAAs alone (p<0.05). Serum insulin concentration was positively correlated with the levels of mTOR, (r=0.923), S6K1 (r=0.814) and 4E-BP1 (r=0.953).ConclusionsIn conclusion, the results of this study provide evidence that the addition of ACr to BCAAs significantly enhances exercise-induced MPS, and the phosphorylation of mTOR signaling proteins, compared to BCAAs and exercise alone.
Keywords: Amylopectin; Chromium; Insulin sensitivity; Muscle protein synthesis; Essential amino acids; Branched-chain amino acids